2002
DOI: 10.1080/mmy.40.1.87.109
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the internal transcribed spacer regions as molecular targets to detect and identify human fungal pathogens

Abstract: Advances in molecular technology show great potential for the rapid detection and identification of fungi for medical, scientific and commercial purposes. Numerous targets within the fungal genome have been evaluated, with much of the current work using sequence areas within the ribosomal DNA (rDNA) gene complex. This section of the genome includes the 18S, 5.8S and 28S genes which code for ribosomal RNA (rRNA) and which have a relatively conserved nucleotide sequence among fungi. It also includes the variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
154
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(162 citation statements)
references
References 193 publications
3
154
0
5
Order By: Relevance
“…with 98 % identity to the ex-type strain of E. aquamarina (CBS 119918) in the 18S rDNA gene was reported as one of the main fungi colonizing a marble monument in Germany (Hallmann et al 2013). In that study, the fungus was identified as E. aquamarina but, taking into account its terrestrial habitat and that 18S is a relatively conserved gene (Iwen et al 2002), almost certainly the fungus on marble represents a different but related taxon. Exophiala radicis was recently described as an endophyte of the brassicaceous host Microthlaspi perfoliatum in Bulgaria, France and Germany, and was also isolated from other plant materials in different European countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with 98 % identity to the ex-type strain of E. aquamarina (CBS 119918) in the 18S rDNA gene was reported as one of the main fungi colonizing a marble monument in Germany (Hallmann et al 2013). In that study, the fungus was identified as E. aquamarina but, taking into account its terrestrial habitat and that 18S is a relatively conserved gene (Iwen et al 2002), almost certainly the fungus on marble represents a different but related taxon. Exophiala radicis was recently described as an endophyte of the brassicaceous host Microthlaspi perfoliatum in Bulgaria, France and Germany, and was also isolated from other plant materials in different European countries.…”
Section: Discussionmentioning
confidence: 99%
“…BLAST searches (Altschul et al 1990) were performed with the ITS and LSU sequences of the strains studied in order to compare them with those of species deposited in GenBank. For molecular species identification, percent identities of just the ITS locus were considered, because it offers a higher resolution than the relatively conserved LSU gene (Iwen et al 2002). If the identity of the ITS sequence of a studied strain to its closest match was ≥99 %, they were considered conspecific (Zeng et al 2007).…”
Section: Dna Sequence Analysesmentioning
confidence: 99%
“…The utilization and the improvement of mycoinsecticides could be an alternative tool to overcome the considerable environmental impact and high economical costs posed by conventional insecticides (Roberts and St. Leger, 2004). The non-transcribed intergenic region (IGS) and the internal transcribed spacers (ITS) located in the nuclear ribosomal DNA (rDNA) gene cluster evolve rapidly and have been widely used as a tool to evaluate the genetic diversity within populations of fungi (Mavridou and Typas, 1998;Pantou et al, 2003;Hughes et al, 2004;Velásquez et al, 2007) and to resolve problems regarding the identification of species and isolates based on morphological characters (Milner et al, 1994;Driver et al, 2000;Iwen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization and the improvement of mycoinsecticides could be an alternative tool to overcome the considerable environmental impact and high economical costs posed by conventional insecticides (Roberts and St. Leger, 2004). The non-transcribed intergenic region (IGS) and the internal transcribed spacers (ITS) located in the nuclear ribosomal DNA (rDNA) gene cluster evolve rapidly and have been widely used as a tool to evaluate the genetic diversity within populations of fungi (Mavridou and Typas, 1998;Pantou et al, 2003;Hughes et al, 2004;Velásquez et al, 2007) and to resolve problems regarding the identification of species and isolates based on morphological characters (Milner et al, 1994;Driver et al, 2000;Iwen et al, 2002).Even though Metarhizium strains have been used in Brazil against a number of insect pests since the 1980s (Garcia et al, 1984), an evaluation on the intraspecific genetic variability of Metarhizium isolates from Brazil has not so far been performed. Since better characterization of the genetic variation within an entomopathogenic fungus population could be useful for the selection of more efficient isolates for biological control, the aim of this study was to assess the extent of genetic variability in the IGS region of Metarhizium strains with special attention placed on the Brazilian isolates.…”
mentioning
confidence: 99%
“…This inability to detect fungi, along with the increased time required to phenotypically identify a fungal species, has led to a proposal to consider molecular biologybased methods for testing (1,6,8,16). Numerous continuousmonitoring blood culture systems have been developed, and molecular approaches to detect microbial pathogens in bottles have shown promise (2, 9-12, 14, 15, 17, 18).…”
mentioning
confidence: 99%